2021
DOI: 10.1002/pc.26333
|View full text |Cite
|
Sign up to set email alerts
|

Flexural strength of foam‐filled polymer composite sandwich panel with novel M‐shaped core reinforced bynano‐SiO2

Abstract: Present article has experimentally determined the flexural strength of carbon fiber reinforced polymer sandwich panel reinforced by nano-SiO 2 with novel M-shaped lattice core. For this purpose, a polymer composite sandwich panel with M-shaped core made of carbon-epoxy fiber has been fabricated in this experiment. In order to fabricate the sandwich panels, the vacuum assisted resin transfer molding has been used to achieve a laminate without any fault.Afterward, polyurethane foam (PU) has been injected into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Months later, exercise was higher at 3 months ( P < 0.01). After 6 months of strenuous exercise, the strength of the Berg Balance Scale combined with Taijiquan group, Taijiquan group, and core muscle group in youth muscle strength training was higher than that of the control group ( P < 0.01) [ 18 ]. After 6 months of exercise, the Taijiquan group had higher muscle training Berg Balance Scale scores than the Taijiquan group and the core muscle group ( P < 0.05).…”
Section: Experimental Analysismentioning
confidence: 99%
“…Months later, exercise was higher at 3 months ( P < 0.01). After 6 months of strenuous exercise, the strength of the Berg Balance Scale combined with Taijiquan group, Taijiquan group, and core muscle group in youth muscle strength training was higher than that of the control group ( P < 0.01) [ 18 ]. After 6 months of exercise, the Taijiquan group had higher muscle training Berg Balance Scale scores than the Taijiquan group and the core muscle group ( P < 0.05).…”
Section: Experimental Analysismentioning
confidence: 99%
“…Finally, the sandwich panels are placed in an oven at 60 o C for 4 h. The final thickness of each laminate is 4 mm. 13 (b) hourglass sandwich panel, 14 (c) pyramidal sandwich panel, 14 (d) sandwich panel with M-shaped core, 19,20 and (e) sandwich panel with lattice core. 21…”
Section: Laminate Productionmentioning
confidence: 99%
“…Using VARTM, Khaledi and Rostamiyan 19 experimentally and numerically investigated the mechanical response of composite sandwich panels with M-shaped lattice core (see Figure 1(d)) subjected to three-point bending and compressive loads. Khaledi and Rostamiyan 20 experimentally determined the flexural strength of carbon-fiber-reinforced polymer sandwich panels reinforced by nano-SiO 2 with an M-shaped lattice core (see Figure 1(d)). Norouzi and Rostamiyan 21 studied the flatwise compression behavior of composite sandwich panels with new lattice cores (see Figure 1(e)) experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] In addition to empty honeycomb cores, there has also been interest in filled cellular cores for sandwich composites, most commonly being polymer foams. [7,8] Chandrasekaran and Arunachalam performed a review of such composites, [9] where they identified that much of this work has been focused on improving the mechanical performance of the panels, namely the energy absorption and through-thickness strength of the composite. While all of the previously mentioned work has been interested in the out-of-plane properties of the honeycomb core, there is also interest in the in-plane properties of honeycomb core.…”
Section: Introductionmentioning
confidence: 99%